Pengaruh Karakteristik Perawat Terhadap Kinerja Perawat yang Dimediasi Motivasi Perawat Puskesmas Pakong Kabupaten Pamekasan - Yayuk Ismi Irawati; Chamariyah Chamariyah; Wasis Budiarto (Digital Bisnis: Jurnal Publikasi Ilmu Manajemen dan E-Commerce, 2024)
The type of research is explanatory, the research approach used is quantitative, the research sample is 56 respondents. Data analysis using SPSS and PLS analysis. The objectives of this study are: 1) To test and analyze whether there is a significant influence of nurse characteristics on the performance of nurses at Pakong Health Center, Pamekasan Regency; 2) To test and analyze whether there is a significant influence of nurse characteristics on the motivation of nurses at Pakong Health Center, Pamekasan Regency; 3) To test and analyze whether there is a significant influence of motivation on the performance of nurses at Pakong Health Center, Pamekasan Regency; 6) To test and analyze whether there is a significant influence of nurse characteristics on the performance of nurses at Pakong Health Center, Pamekasan Regency mediated by motivation. The results of the study indicate that: 1) Nurse characteristics have a significant effect on the performance of nurses at the Pakong Health Center in Pamekasan Regency with an original sample value of 0.324; 2) Nurse characteristics have a significant effect on the motivation of nurses at the Pakong Health Center in Pamekasan Regency with an original sample value of 0.421; 3) Motivation has a significant effect on the performance of nurses at the Pakong Health Center in Pamekasan Regency with an original sample value of 0.435; 6) Nurse characteristics have a significant effect on the performance of nurses at the Pakong Health Center in Pamekasan Regency mediated by motivation with an original sample value of 0.183.